Cognitive Behavioral Therapy to Improve Life Quality and Blood Stability - Adriani, Rita Benya; Handayani, Siti; Prabowo, Tri (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes is a severe chronic disease, ranked third out of four world non-communicable diseases. The prevalence of type 2 diabetes mellitus (DM) in Indonesia is 1.6 million and in Surakarta is 9484. This research aimed to determine the effect of cognitive behavioral therapy (CBT) in improving the life quality and blood sugar stability of patients with type 2 DM. The quasi-experimental (pre-test–post-test control group design) method used 84 subjects taken purposively. The results of the univariate analysis in the experimental and control groups showed that most of the subjects were housewives with high school education and some with an undergraduate degree. The participants were mostly women aged 51–60 years old, height 151–160 cm and body weight 51–60 kg. The results of the bivariate analysis showed that CBT could improve the life quality of patients with type 2 DM (p = 0.001); CBT can also help to stabilize fasting blood sugar (p = 0.023) and current blood sugar (p = 0.001). Health workers can help to change the mindset, beliefs and maladaptive behavior of DM patients using DM management.